CFO Gender, Corporate Risk-Taking, and Information Disclosure Violations - Zhao, Yujie; Xiong, Jiaxin; Wang, Jingjing; Ye, Nanji (Frontiers in Psychology, 2022)
The sex ratio at birth in China exhibits a major occurrence of "missing women" due to the high son preference in Chinese culture. Clearly, the large gender discrepancy in China cannot be explained solely by ethical, moral, or social fairness theories, but also by the economic benefits of women's particular abilities, experiences, and talents. This article examines the influence of female CFOs on information disclosure violations in order to highlight women's positive contributions. Our data imply that having a female CFO can dramatically lower the number of companies that fail to disclose information. The results are strong after controlling endogeneity with PSM, Heckman two-stage self-selection model, and CFO change, as well as controlling the gender of the Chairman and CEO, utilizing different study periods, and using exogenous shock. We further examine the moderate effects of CFO power and external monitoring, and we find that CFO power magnifies the negative effect of female CFO on violations, and the more the power, the more negative effect of female CFO on violations. We also find that when the firm has effective external monitoring, there are fewer future infractions of information disclosure.